Comparison of phenol removal with ozonation in jet loop reactor and bubble column - Barlak, Melahat Semin; Degermenci, Nejdet; Cengiz, Ibrahim; Ozel, Handan Ucun; Yildiz, Ergun (Elsevier BV, 2020)
Abstract This study aimed to remove phenol with ozonation in a jet loop reactor (JLR) and a bubble column (BC). In the first stage of the study, the mass transfer properties of JLR were determined and superiority over BC reactors were shown, and in the second stage, these reactors were used in phenol removal studies. At the same conditions, the volumetric mass transfer coefficient of JLR was 0.540 min-1, while this value was determined as 0.246 min-1 in the BC reactor. In phenol removal, the effects of initial phenol concentration, ozone dosage and pH on phenol and chemical oxygen demand (COD) removal were determined for both JLR and BC. While the pseudo-first rate constant for phenol removal in JLR at 221 mg/min ozone dosage was 0.1756 min-1, this value was only calculated as 0.1157 min-1 in the BC reactor. As a result, it has been shown that JLRs can achieve higher ozone gas transfer with lower energy consumption and perform more effective phenol and COD removal than BC reactors, especially at low pH and high ozone dosages.
Keywords: Bubble Column; Phenol; Chemical Oxygen Demand; Process Chemistry and Technology; ozonation; jet loop reactor; Jet Loop Reactor; chemical oxygen demand; Ozonation; bubble column; 7. Clean energy; 6. Clean water